2019
DOI: 10.1002/hep.30304
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitors Are Associated With Minimal and Overt Hepatic Encephalopathy and Increased Mortality in Patients With Cirrhosis

Abstract: Minimal hepatic encephalopathy (MHE) is a subclinical cognitive impairment frequently observable in patients with cirrhosis. Proton pump inhibitors (PPIs) can contribute to small‐bowel bacterial overgrowth, but no study has investigated the link between PPIs and MHE. We investigated the relationship between MHE and PPI use as well as the role of PPI use in the development of overt HE and survival. Consecutive patients with cirrhosis (n = 310) were included in the study and followed up for 14.1 ± 12.3 months. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 51 publications
5
90
1
1
Order By: Relevance
“…PPIs are widely used in cirrhotic patients and are associated with poor outcomes, in part due to infections and HE. 72 PPI use can be associated with increased relative abundance of oral-origin microbiota in the distal gut after as little as 14 days of omeprazole in healthy individuals and in patients with compensated and decompensated cirrhosis. 73 These have functional consequences with ureaseproducing Streptococcaceae and higher trimethylamine N-oxide (TMAO) generation.…”
Section: Composition and Functional Changes In Microbiota In Patientsmentioning
confidence: 99%
“…PPIs are widely used in cirrhotic patients and are associated with poor outcomes, in part due to infections and HE. 72 PPI use can be associated with increased relative abundance of oral-origin microbiota in the distal gut after as little as 14 days of omeprazole in healthy individuals and in patients with compensated and decompensated cirrhosis. 73 These have functional consequences with ureaseproducing Streptococcaceae and higher trimethylamine N-oxide (TMAO) generation.…”
Section: Composition and Functional Changes In Microbiota In Patientsmentioning
confidence: 99%
“…Given mounting interest in sarcopenia as a general risk biomarker in cirrhosis, such studies are likely highly feasible by collecting data on new HE (and other decompensations) in addition to conventional outcomes such as transplant‐free survival. Medication burden is also associated with the development of HE. Previous studies have implicated proton pump inhibitors, benzodiazepines, and nonselective betablockers . Whether these findings causally related or correlated is debatable.…”
Section: Predicting the Risk Of Overt He Along The He Risk Pathwaysmentioning
confidence: 99%
“…These findings underline the potential over prescription of this class of drugs and at least half of the patients in these studies seem to have no indication for a long‐term PPI therapy 11 . Additionally, emerging evidence points towards an association of PPI use with infections as well as the development of hepatic encephalopathy in patients with cirrhosis 11,15,16 …”
Section: Discussionmentioning
confidence: 77%
“…This is mostly explained by impaired visuomotor coordination, reaction time, psychomotor speed and attention 25 . A recent study by Nardelli et al demonstrated that PPI use may increase the prevalence of minimal hepatic encephalopathy and the incidence of overt hepatic encephalopathy 16 . Therefore, it seems possible that PPI use may result in a higher frequency of falls, explanatory of increased risk of fractures.…”
Section: Discussionmentioning
confidence: 99%